Dynamic Performance and Analysis of Direct Torque Control Method Based on DSP for PMSM Drives - Ozcira, Selin; Bekiroglu, Nur; Senol, Ibrahim (IEEE, 2012)
This paper presents theoretical analysis and experimental verification of the direct torque control (DTC) for permanent magnet synchronous motor (PMSM) drive. PMSM drive is characterized by the direct torque control based on space vector pulse-width modulation (SVPWM) method which is controlled by digital signal processor (DSP). Since the constant switching frequency is produced by SVM technique, the space vector PWM control method enables the drive to produce voltage vector of any direction and magnitude thus, torque ripple is eliminated compared with classical hysteresis DTC. The proposed DTC method includes simplified reference flux vector calculator and torque estimator introducing space vector pulse-width modulation (SVPWM) method. Experimental results obtained by a motor&generator setup are shown to verify the operating principle and performance. As a result, the experimental setup exhibits validity of the analysis and to demonstrates good dynamic response.
Keywords: permanent synchronous motor; direct torque control; digital signal processor; MOTOR-DRIVES; SALIENCY; Energy & Fuels; Engineering